Case report: Germline BRCA 2 mutation in primary peritoneal carcinoma: a rare malignancy - Huang, Yan-Ying; Zhang, Yue; Xie, Wen-Jun (Frontiers in Oncology, 2024)
BackgroundPrimary peritoneal carcinoma (PPC) is a rare malignancy. Clinically, its histological morphology resembles that of epithelial ovarian tumors (EOC), often leading to misdiagnosis. Diagnosis and treatment of PPC are time-sensitive because of the rapidly progressive nature of the disease.Case reportHerein, we report the case of a 54-year-old woman who was initially diagnosed with ovarian cancer; however, extensive workup showed evidence of Müllerian PPC origin. Furthermore, the patient harbored a targetable BRCA mutation.ConclusionThe patient was treated with the BRCA-targeting agents and had a good prognosis after surgery.